Solid-State Organometallic Chemistry (SMOM): synthesis, alkane dehydrogenation and surface modification of crystalline σ-alkane complexes - Bukvic, AJ (2020)
This thesis reports the synthesis of single-crystalline σ-alkane complexes of rhodium. These are synthesised by the hydrogenation of precursor alkene or diene complexes in solid/gas single-crystal to single-crystal (SC-SC) transformations, using the Solid-State Molecular OrganoMetallic (SMOM) methodology developed by the Weller group.